INTERPRETABLE MACHINE LEARNING DENGAN PENDEKATAN MODEL AGNOSTIK PADA PREDIKSI FUEL CONSUMPTION RATE MINING HAUL TRUCK - Arbianto, Domy Guruh Dwi; Purnomo, Jerry Dwi Trijoyo (Smart Education, 2026)
Abstract: Machine learning (ML) models are frequently characterized as